PENGARUH BEBERAPA VARIABEL EKONOMI MAKRO TERHADAP PROFITABILITAS DAN RETURN SAHAM PADA INDUSTRI PERBANKAN DI BEI - Sidhi Adiyadnya, I Nyoman; Sri Artini, Luh Gede; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.08. TAHUN 2016, 2016)
This study aims to clarify the influence of several macroeconomic variables on the profitability of the banking industry and stock returns in the Indonesia Stock Exchange. The population of this study is the entire banking sector companies listed on the Indonesia Stock Exchange during the 2008-2013 which consisted of 36 companies. Several macroeconomic indicators in this study were measured through the rate of inflation, GDP, and the dollar exchange rate. Microeconomic indicators that reflect the company's financial performance is profitability. Profitability ratios measured by ROE (Return On Equity) reflects the company's ability to generate available profit for the owners of the company on the capital they invest in the company. The sampling method used was purposive sampling method with the specified criteria. Therefore, the number of samples used in this study is 26 companies. The data of this study are secondary data obtained from the Indonesian Capital Market Directory of 2008-2013 and two websites www.bi.go.id and www. idx.co.id. Path Analysis was used to analyze the statistical data using SPSS 16.0. The results of this study indicates that: (1) the inflation rate acted negatively not significant towards profitability, (2) GDP acted positively significant towards profitability, (3) the dollar exchange rate acted negatively not significant towards profitability, (4) The inflation rate acted negatively not significant towards share returns, (5) GDP acted negatively not significant effect on share returns, (6) the dollar exchange rate acted positively not significant towards share returns, (7) Profitability acted positively significant towards share returns.
Keywords: Keywords : Stock return, profitability, macroeconomic variables